Cherenkov diffraction radiation generated by 3D printed plastic samples; Young Scientists and Specialists (AYSS-2024) - Kubankin A. S. Aleksandr Sergeevich; Bulavskaya A. A. Angelina Aleksandrovna; Baldin A. A. Anton Aleksandrovich; Klenin A. A. Artemy; Kidanova E. A. Ekaterina Alekseevna; Bushmina E. A. Elizaveta Alekseevna; Kishin I. A. Ivan; Nozdrin M. A. Mikhail; Karataev P. V. Pavel Vladimirovich; Alekseev S. V. Sergei; Stuchebrov S. G. Sergey Gennadevich; Kocharian (Kocharyan) V. R. Vagan Rashidovich; et al. (2024, 2024)
The generation of polarization radiation by electron beams passing near dielectric objects is attracted the attention of researchers due to the potential for introducing this effect to either measure the beam parameters or generate intense electromagnetic radiation beams in THz and sub-THz frequency range. One of the most interesting forms of this radiation is Cherenkov diffraction radiation (ChDR), which arises when high-energy electrons traverse along a dielectric edge. The characteristics of the generated radiation are dependent on the properties of the charged particles